2020
DOI: 10.1007/s00701-020-04445-z
|View full text |Cite
|
Sign up to set email alerts
|

“Black bone”: the new backbone in CAD/CAM-assisted craniosynostosis surgery?

Abstract: Background Computer-assisted design and manufacturing (CAD/CAM) techniques have been implemented in craniosynostosis surgery to facilitate cranial remodeling. However, until now, computed tomography (CT) scans with ionizing radiation were necessary to plan the procedure and create guiding templates. The purpose of this study was to present our series using CAD/CAM techniques in planning and conducting fronto-orbital advancement surgery in patients with trigonocephaly with datasets acquired only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Specific clinical applications recently reported include guided dental implant surgery, 32,51,52 trauma surgery, 30 orthodontic treatment planning, 21 and craniosynostosis surgery. 53 Practical limitations to the use of MR imaging in dental and craniofacial applications include the presence of motion and susceptibility artifacts, some contraindications such as the presence of pacemakers or neurostimulators, and limitations in terms of extended cost and availability.…”
Section: Discussionmentioning
confidence: 99%
“…Specific clinical applications recently reported include guided dental implant surgery, 32,51,52 trauma surgery, 30 orthodontic treatment planning, 21 and craniosynostosis surgery. 53 Practical limitations to the use of MR imaging in dental and craniofacial applications include the presence of motion and susceptibility artifacts, some contraindications such as the presence of pacemakers or neurostimulators, and limitations in terms of extended cost and availability.…”
Section: Discussionmentioning
confidence: 99%
“…CT imaging is the standard technique used for the generation of 3D models of the cranium prior to surgery. However, a new MRI technique called "black bone" has already been validated as a reference for CAD/CAM craniosynostosis surgery [47]. Therefore, MRI could be used to avoid CT scans and the exposure of the infants to ionizing radiation.…”
Section: Computer-aided Design and Manufacturingmentioning
confidence: 99%
“…The superior imaging quality of CT scans on cortical bones and the possibility of creating 3D reconstructions were one of the major limitations of wider applicability of MRI, but advancements in technologies are working hard to propose MRI as a no-radiation alternative in this field. New protocols, such as black-bone imaging, can provide high-quality 3D imaging of bones and sutures similar to those of CT, while giving, in the same session, details about structural anomalies and prognostic information [ 38 , 39 ]. Eley et al first reported the black-bone imaging technique in literature in 2012 [ 40 ]; thanks to short TE/TR and low flip angle, it makes it possible to minimize soft-tissue contrast to enhance the bone-soft tissue interface.…”
Section: Future (2010–2021): New Applications and Possibilitiesmentioning
confidence: 99%
“…Patent sutures have a different signal intensity than prematurely fused ones [ 41 ]. Moreover, it is possible to provide 3D-reconstructed images and, also, to create 3D models using a 3D printing [ 39 , 41 ].…”
Section: Future (2010–2021): New Applications and Possibilitiesmentioning
confidence: 99%